KARAKTERISTIK EDIBLE FILM YANG DIPRODUKSI DARI KOMBINASI GELATIN KULIT KAKI AYAM DAN SOY PROTEIN ISOLATE - , MUHAMAD HASDAR, S.PT ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study was aimed to combine chicken legs skin gelatin and soy protein isolate as a raw material for edible films. This research materials were used chicken leg skin and soy protein isolate. The experimental was divided into two stages. The first stage was processing of gelatin from chicken leg skin which soaked in 0.1% NaOH, 0.1% sulfuric acid, and 0.4% citric acid. The second stage was preparation of edible films. The material films were combination of soy protein isolate and gelatin chicken legs skin in various ratio (75:25, 80:20, 85:15, 90:10, and 95:5). Statistical analysis were carried out by one Anova and the mean difference was tested using Duncan's Multiple Range Test. SDS-PAGE result showed the band pattern of the molecule was dominated by the protein molecules of gelatin, SDS-PAGE pattern showed no changed of bands the type Î±1 and Î±2 of edible films. The results of the analysis of amino acid content of edible films using HPLC produced the largest amino acid residue composition in each treatments is glysin ie 29.42%, 37.88%, 38.32%, 39.28% and 39.17% respetively. This result described that protein profile of HPLC was dominated protein from chicken leg gelatin. Observations with a scanning electron microscope have showed the cross-linking between protein molecules of gelatin and soy protein isolate. Different combinations of chicken legs skin gelatin and soy protein was not different on the tensile strength, and elongation, but there were a significant difference on the thickness and water vapor transmission rate. The fines quality of edible films formed on 95:25.